Study of Experimental Vibration Due to Misalignment of Pulley-Belt in Rotary Machine - Asmara Yanto; Anrinal; Rozi Saferi; Zultri Memori (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2020)
This study aims to investigate the vibration of rotary machine due to misalignment of its pulley-belt, experimentally. Here, the rotary machine is driven by an AC motor with pulley-belt transmission that positioned on the outer portion of shaft-rotor. To generate vibration of rotary machine, pulley-belt is conditioned to have a combination of offset and angular misalignments. Offset misalignment variations are 0, 2, 4, and 6 mm and angular misalignment variations are 0ᵒ, 2ᵒ, 4ᵒ, and 6ᵒ. Vibration of rotary machine is measured on the bearing housing by use MEMS-based accelerometers. The measured signal of vibration acceleration is acquired with a data acquisition device to obtain vibration spectrum. From the investigation to vibration spectrum has been done, it can be concluded that vibration of rotary machine has characteristic with dominant frequencies at 1xRPM of shaft and at 1xRPM of motor. The vibration amplitude at 1xRPM of shaft is higher than the vibration amplitude at 1xRPM of motor. From this investigation, it is not possible to find differences in the characteristics of vibrations significantly that occur between vibrations due to offset misalignment, angular misalignment or their combination.